Halal certification of commercial foodservice industry in Malaysia / Nur Syahirah Abdul Malek and Syahirah Mohamed - Abdul, Nur Syahirah; Mohamed, Malek Syahirah (2021)
The demand of Halal certification has increased in the recent years with an increasing number of Muslim populations and vital in promoting the satisfaction, confidence and trust among consumers. It has become a strategic way in many industries to attract customers. Halal certification is important for the growth of businesses in the food industry, however many entrepreneurs still do not have that certificate in their organization. The aim of this study is to identify the inhibiting factors of commercial foodservice industry in applying Halal certification. In specific, the objective is to identify the most inhibiting factors of commercial foodservice industry in applying Halal certification. Furthermore, the areas that are being selected in conducting this research are hotels, restaurants and Small and Medium Enterprises (SMEs). Then, the methodology utilized is content analysis while secondary data is used to gather previous-collected information. From the findings, the factors that were identified are awareness, staffs, procedure, financial, product and government factor. Based on past researches, the most inhibiting factors is the procedure factor. This study could provide new knowledge regarding Halal certification and help the Government to review the application procedures in order to ease and help most companies to get Halal certification.